PENGARUH MEDIA GAMBAR TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS I SD NEGERI 105288 SEI ROTAN - Leony Cecilia Manurung; Nurmayani; Halimatussakdiah; Elvi Mailani; Tiarnita M.S Br Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of digital picture media on the beginning reading ability of first-grade students at SD Negeri 105288 Sei Rotan in the 2025/2026 academic year. This research employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The population consisted of 41 students selected through a total sampling technique, including 21 students in the experimental class and 20 students in the control class. Data were collected through reading ability tests, observations, and documentation. The research instrument was tested for validity and reliability, resulting in 15 valid items with a reliability coefficient of 0.745. Data analysis was conducted using normality tests, homogeneity tests, and an Independent Sample t-test. The results showed that the average pretest score of the experimental class was 49 and increased to 86 in the posttest, while the control class increased from 48.4 to 72.3. The hypothesis test results showed that the tcount was 5.675 > ttable 2.023 with a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Therefore, digital picture media had a significant effect on students’ beginning reading ability. Digital picture media effectively improved students’ abilities in recognizing letters, reading syllables, words, and simple sentences.